-16-4(-5m+11)=17m

Simple and best practice solution for -16-4(-5m+11)=17m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -16-4(-5m+11)=17m equation:



-16-4(-5m+11)=17m
We move all terms to the left:
-16-4(-5m+11)-(17m)=0
We add all the numbers together, and all the variables
-17m-4(-5m+11)-16=0
We multiply parentheses
-17m+20m-44-16=0
We add all the numbers together, and all the variables
3m-60=0
We move all terms containing m to the left, all other terms to the right
3m=60
m=60/3
m=20

See similar equations:

| 5v=v+33 | | 2t-16=3t-32 | | 7x+200=11x+80 | | 19x-12=8x-23 | | (t)=-16t^+50t+3.5 | | 8x+6=5x–12 | | 20x+16=0 | | 72+c-27=13c+9 | | +2x+6=20 | | 18u-6=16u | | X÷4=2x-16 | | 10t=-120 | | 7x2x-7=35 | | S+29=3s-32 | | X+19+3x=-5-13x-11 | | S+29=3s-33 | | +2x+5=3 | | 7|2x-7|=35 | | F(-5)=-4c+16 | | 27z=54 | | F(4)=-4c+16 | | 2t+23=t+41 | | 5(5x+84)=4(x+63) | | U=2u-19 | | g·3=0.9 | | 8x-2=5x-13 | | 6x-7=-35 | | 13x-7x=88+62 | | 32=4(3x−4) | | -24j=-96 | | +4x-16=2 | | 0.0016=0.92^x |

Equations solver categories